Exploring the Themes of Greed and Selfishness in Nollywood Movie: Soole - Atinuke Olubukade Akintayo; Olugbenga Charles Adewale; Favour Olamide Soyobi (Britain International for Academic Research (BIAR) Publisher, 2026)
This research explores greed and selfishness in Nollywood movie, Soole by Adunni Ade, with a focus on how Nigeria's economic and social developments have not diminished the deep-rooted presence of both greed and selfishness leading to corruption. The research investigates how these vices, are reflected through the characters and narrative structure of the film. Set primarily on a public bus journey, Soole presents a microcosm of Nigerian life, exposing the moral decay and self-centered behaviours that arrive in moments of desperation and opportunity. Using a qualitative research design, the study employs thematic analysis to examine scenes, dialogues, and character interactions in order to identify recurring patterns of greed and selfishness. The film is analyzed both as a cultural artifact and a moral commentary that mirrors Nigeria’s socio-political realities, including corruption, inequality and ethical decline. The findings reveal that Soole serves not only as entertainment but also as a powerful tool for social reflection and ethical discourse. By portraying the consequences of selfish behaviour, from betrayal to tragedy, the film encourages viewers to reassess personal and societal values. This research contributes to the broader academic conversation on Nollywood’s role in shaping public consciousness and promoting moral accountability through storytelling.